Assessment of the Effects of Flow Rate and Ionic Strength on the Performance of an Air-Cathode Microbial Fuel Cell Using Electrochemical Impedance Spectroscopy - Doug Aaron; Costas Tsouris; Choo Y. Hamilton; Abhijeet P. Borole (Energies, 2010)
Impedance changes of the anode, cathode and solution were examined for an air-cathode microbial fuel cell (MFC) under varying conditions. An MFC inoculated with a pre-enriched microbial culture resulted in a startup time of less than ten days. Over this period, the anode impedance decreased below the cathode impedance, suggesting a cathode-limited power output. Increasing the anode flow rate did not impact the anode impedance significantly, but it decreased the cathode impedance by 65%. Increasing the anode-medium ionic strength also decreased the cathode impedance. These impedance results provide insight into electron and proton transport mechanisms and can be used to improve MFC performance.